Advances in In Situ Characterization Techniques for Failure Mechanisms of Zinc Anode Interfaces - Di Zhang; Hongfei Lu; Chenxu Duan; Xinyao Yuan; Zhenjie Zhu; Yi Qin; Yuhang Song; Yang Jin (Energy Material Advances)
Aqueous zinc-ion batteries are considered an ideal choice for energy storage technology in new power systems due to their high theoretical capacity, high safety, and environmental friendliness. However, in practical applications, Zn anodes face a series of problems and challenges, such as Zn dendrite irregular growth, electrode cross-section corrosion, and hydrogen reduction side reactions. This has importantly impeded the large-scale utilization of zinc-ion batteries. Therefore, it is necessary to characterize the failure mechanism of zinc-metal anodes, but the current failure mechanism of Zn anodes is not well characterized, leading to different mechanism elaborations. Although many studies have been conducted to improve the interfacial stability of Zn-metal anode interfaces, there are few systematic summaries of the key role played by in situ characterization in revealing the interfacial mechanisms of Zn-metal anodes. In this paper, the main problems and failure mechanism of zinc anode interface are discussed. Then, the application of in situ characterization technology in zinc anode interfaces and the latest research progress are summarized from different aspects. The purpose of this review is to better understand the development of zinc-ion batteries and the improvement of the stability of the Zn anode interface, thus accelerating the large-scale production of zinc batteries. Finally, the research direction of the in situ characterization of zinc anodes is summarized and suggested.